PEMELIHARAAN FASILITAS DAN INFRASTRUKTUR DI SEKOLAH - Masduki Ahmad (Akademika, 2021)
The aim of this study is to discover and obtain information about the upkeep of educational facilities and infrastructure at Vocational High School 2 Cikarang Barat. The analysis method used is descriptive qualitative. The study took place at Vocational High School 2 Cikarang Barat from July 2020 to December 2020. The school principal, deputy headmaster in charge of facilities and infrastructure, maintenance support staff, and students of Vocational High School 2 Cikarang Barat served as research informants. Interviews, observation, and reporting studies are all used to collect data. After that, the data is analyzed by reducing it, presenting it, and drawing conclusions. The triangulation of sources, techniques, and hypotheses is a validity technique. The study's findings indicate that: (1) Vocational High School 2 Cikarang Barat maintenance preparation starts with a work meeting, and then maintenance is divided into two categories: normal and routine maintenance. A one-year budget is generated after deciding maintenance tasks based on their categories. Following that, representatives from the facilities and infrastructure sector specifically select the structure of facility and infrastructure maintenance, as well as their respective job desks in each division, which are known to the school principal. The final move is to socialize students at school. (2) School maintenance processes and techniques begin with frequent and routine maintenance. Routine maintenance includes the upkeep of classrooms, teacher's offices, and special rooms such as libraries, computer laboratories, and science labs. The school also performs routine maintenance on air conditioners, printers, and photocopiers, as well as computer program upgrades. (3) Obstacles faced by schools in preparing facility and infrastructure repairs, including, among other problems, things that arise unexpectedly and need urgent repair at the facility. The lack of knowledge of users of school facilities and infrastructure, partners with outsiders who are often less sensitive, and cultural differences among individuals in the use of facilities and infrastructure are among the process and technological obstacles encountered.